2017
DOI: 10.1038/srep43995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionizing radiation on the proliferation of human embryonic stem cells

Abstract: We studied the effect of ionizing radiation (IR) on continuous growth of seven hESC lines. Cells were exposed to 0, 0.2, or 1 Gy of X-rays, and the growth rates of cell populations were assessed by measuring areas of the same individual colonies versus time. The population doubling times (DT) of sham-irradiated cells varied from 18.9 to 28.7 hours for different cell lines. All cell lines showed similar reaction to IR, i.e. cell populations dropped within 24–48 hours post IR; after that they recovered and grew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…We also found that the difference between hESC maintenance culture in standard tissue culture plates and the microfluidic device in a static condition was not significant ( p >0.05). The doubling time for hESC H9 in both culture systems matched that reported in the literature (doubling time: 24.2 h) [14] .
Fig.
…”
Section: Methodssupporting
confidence: 85%
“…We also found that the difference between hESC maintenance culture in standard tissue culture plates and the microfluidic device in a static condition was not significant ( p >0.05). The doubling time for hESC H9 in both culture systems matched that reported in the literature (doubling time: 24.2 h) [14] .
Fig.
…”
Section: Methodssupporting
confidence: 85%
“…Viability of hESCs after exposure to radiation was similar to that reported previously [29]. Herein, the reaction of hESCs to CT irradiation was assessed by the expression of pluripotency marker OCT4 and the DNA repair foci marker 53BP1 [19].…”
Section: Methodssupporting
confidence: 55%
“…Stem cell proliferation rate depends on multiple factors including genetic background, culture media and conditions, and passage number (Park et al, 2008). For instance, reported doubling times for H9 hESCs vary from around 24 h (Panyutin et al, 2017) to 133 h for a microcarrier culture study (Badenes et al, 2016). Compared to the other hPSC lines, H9 hESCs here exhibiting a greater expansion rate and a decline from a peak concentration of ∼27 × 10 5 cells/ml a day after commencement of the differentiation to ∼20 × 10 5 cells/ml at the end.…”
Section: Discussionmentioning
confidence: 99%